Optimization of the Marketing Mix in Enhancing the Competitiveness of Local Products in the Global Market - Sobar, Agus (GoAcademica Research & Publishing, 2025)
Local products face major challenges in entering the highly competitive global market. The lack of optimization of marketing strategies has resulted in many local products being unable to compete effectively with global products. In this context, the marketing mix becomes a crucial instrument for increasing competitiveness at the international level. This study aims to analyze how marketing mix strategies can be optimized to strengthen the position of local products in the global market. This study employs a qualitative approach, drawing on data from various relevant studies and publications that discuss local product marketing strategies and export challenges. Data is analyzed thematically to find strategic patterns that can be applied widely. The results of the study show that adjusting product characteristics to global market tastes, adaptive pricing, efficient distribution, and integrated promotions are key to increasing competitiveness. Promotion strategies that highlight cultural values ​​and use a digital approach have proven effective in building a global product image. With proper marketing mix management, local products have a great opportunity to develop sustainably in the international market.